Dopaminergic system genes in ADHD: toward a biological hypothesis - GILL, MICHAEL; HAWI, ZIARIH; MCCARRON, MARY (My University, 2002)
Converging evidence has implicated abnormalities of dopamine neurotransmission to the pathology of attention deficit hyperactivity disorder (ADHD). Several genetic association studies have been published, but so far, no DNA variants have been unequivocally demonstrated as contributing to ADHD susceptibility. Four dopamine related gene loci have been implicated, however: DAT1, DRD4, DBH, and DRD5. Each of these may influence the liability of ADHD to a small degree. Notably, all are involved in signal transduction at the neuronal synapse. In this article, we investigate as candidate genes for ADHD, DNA polymorphisms at dopamine receptors, the dopamine transporter, and genes known to be involved in dopamine synthesis and metabolism. In a recent article, we confirmed the previously reported association of DAT1 (480bp allele) with ADHD and identified polymorphisms at two additional loci showing preferential transmission to ADHD children of alleles at DRD5 (148bp allele) and at DBH (allele 2, Taq I polymorphism). Increased transmission of the 4bp deletion in the untranslated exon 1 of the DOPA decarboxylase gene was also observed but was of marginal significance. Nonsignificant trends of association were found for TH (allele 2) and DRD2 (Ser-311). No preferential transmission of alleles to ADHD children was observed for polymorphisms at DRD1, DRD2 (TaqI), DRD3, DRD4, and COMT. Analyzing the data by sex of transmitting parent showed significant preferential paternal transmission of alleles at TH (allele 2) and a nonsignificant trend for paternal transmission for DRD2 (Ser-311). We attempt to put these findings together with what is known of the function of the particular proteins, and suggest working hypotheses.
PUBLISHED
PMID: 12377397
Keywords: Attention deficit hyperactivity disorder; Dopamine receptors; Candidate genes; Dopamine transporter; Haplotype-based haplotype relative risk; Transmission Disequilibrium Test; Imprinting